Diagnosis and Management of Devic’s Disease - Desrina Desrina; Syntia Nusanti; M. Sidik (Majalah Oftalmologi Indonesia, 2015)
Background: To report diagnosis and management of Devic’s Disease with good visual outcome.Case Illustration: A 51 years-old male came with sudden blurred vision of his right eye since 3 days.The patient also complained of lower limbs weakness, urinary retention, and defecation disorder.Ophthalmology examination revealed visual acuity of no light perception in the right eye and 6/12 inthe left eye. Light reflex of both eyes decreased. Funduscopy examination of the right eye showed anindistinct edge and hyperemic optic nerve head, cup-disc ratio was hard to be evaluated, artery/vein ratioof  2/3, macular reflex was positive and the retina was good. Funduscopy of the left eye was within normallimit. No pathological finding in brain Magnetic Resonance Imaging (MRI). Thoracolumbal MRI supportlongitudinal transverse myelitis. The patient was diagnosed as Devic’s Disease and treated initiallywithintravenous methylprednisolone 1 g/day for five days followed by methyl prednisolone orally.Conclusion: Early diagnosis of Devic’s Disease is important because immediate therapeutic interventionis required to get excellent result, prevent relapse and further disability.